2015
DOI: 10.11648/j.ajrs.20150302.12
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Land use Around the Micro-Dam Anti-Salt in the Sub-Watershed of Agnack Lower Casamance (Senegal)

Abstract: Agriculture, mainly based on rain, is one the most important economic activities in Lower Casamance region. Its agricultural production is vulnerable to climatic variability. The water management has become an important issue for rural populations food security. This research aims at the characterization of environmental evolution and agricultural production, around the anti-salt micro-dams in Lower Casamance area, which has a high rainfall and a rich potential of water resources. This study examines the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Different studies conducted under pot or field conditions have indicated that appropriate agronomic management increases rice production in ASS. To cope with iron toxicity, several strategies have been proposed: add mineral fertilisers to improve soil fertility [38]; apply phosphogypsum and lime to increase available Ca and soil pH and lower toxic iron and aluminium levels [34,39,52]; add organic residue, which could stimulate the activity of reducing bacteria [32] to lead to a rise in pH under flooded conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies conducted under pot or field conditions have indicated that appropriate agronomic management increases rice production in ASS. To cope with iron toxicity, several strategies have been proposed: add mineral fertilisers to improve soil fertility [38]; apply phosphogypsum and lime to increase available Ca and soil pH and lower toxic iron and aluminium levels [34,39,52]; add organic residue, which could stimulate the activity of reducing bacteria [32] to lead to a rise in pH under flooded conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative results of the land-use dynamics based on satellite data showed a significant decline in the rice area for 1984-2010 in the subwatersheds of the lower Casamance basin. However, increased rainfall reversed this trend between 2000 and 2010 [32].…”
Section: Introductionmentioning
confidence: 93%